Fenfluramine significantly reduces day‐to‐day seizure burden by increasing number of seizure‐free days and time between seizures in patients with Dravet syndrome: A time‐to‐event analysis. Issue 1 (22nd October 2021) - Sullivan, Joseph; Specchio, Nicola; Devinsky, Orrin; Auvin, Stéphane; Perry, M. Scott; Strzelczyk, Adam; Gil‐Nagel, Antonio; Dai, David; Galer, Bradley S.; Gammaitoni, Arnold R.
Abstract: Objective: The number, unpredictability, and severity of seizures experienced by patients with Dravet syndrome (DS) negatively impact quality of life (QOL) for patients, caregivers, and families. Metrics are needed to assess whether patients with residual seizures have moved meaningfully toward seizure freedom after treatment with new antiseizure medications. Methods: We evaluated the time required postrandomization for each patient to experience the same number of seizures experienced during baseline (i.e., time‐to‐ n th seizure), using a post hoc time‐to‐event (TTE) analysis of data from two Phase 3 placebo‐controlled trials of adjunctive fenfluramine for DS (Study 1, N = 119; Study 2, N = 87). Patients aged 2–19 years were randomized to placebo or adjunctive fenfluramine (Study 1: .7 mg/kg/day or .2 mg/kg/day; Study 2: .4 mg/kg/day with stiripentol). Data were analyzed by Kaplan–Meier TTE curves and waterfall plots. Results: The proportion of patients who never reached baseline seizure frequency was greater with fenfluramine than with placebo (Study 1: fenfluramine .7 mg/kg/day, 60%; fenfluramine .2 mg/kg/day, 31%; placebo, 13%; Study 2: fenfluramine .4 mg/kg/day, 58%; placebo, 2%). Median time‐to‐ n th seizure was longer after fenfluramine than after placebo (Study 1: fenfluramine .7 mg/kg/day, 13 weeks; .2 mg/kg/day, 10 weeks; placebo, 7 weeks; Study 2: fenfluramine .4 mg/kg/day, 13 weeks; placebo, 5 weeks; p < .001). Longest duration of convulsive seizure‐free days was increased in active groups versus the placebo group (Study 1: fenfluramine .7 and .2 mg/kg/day, 25.0 and 15.0 days; placebo, 9.5 days [ p = .0001; p = .0352]; Study 2: fenfluramine .4 mg/kg/day, 22.0 days; placebo, 13.0 days [ p = .004]). The most common adverse events included decreased appetite, pyrexia, upper respiratory tract infection, diarrhea, and fatigue. Significance: These data demonstrate that fenfluramine can significantly reduce day‐to‐day seizure burden in patients with DS, providing prolonged periods of convulsive seizure‐free days, which may help reduce the physical and emotional disease toll while improving health‐related QOL for patients and caregivers.